2009
DOI: 10.1016/j.chemgeo.2008.10.034
|View full text |Cite
|
Sign up to set email alerts
|

Hydrocarbons and oxidized organic compounds in hydrothermal fluids from Rainbow and Lost City ultramafic-hosted vents

Abstract: The first building blocks of life could be produced in ultramafic-hosted hydrothermal systems considering the large amounts of hydrogen and methane generated by serpentinisation and Fischer-Tropsch-Type synthesis, respectively, in those systems. The purpose of this study was to detect and characterise organic molecules in hydrothermal fluids from ultramafic-hosted hydrothermal systems in the Mid-Atlantic Ridge (MAR) region. During the EXOMAR cruise 2005, fluids from the Rainbow (36°14′N) and the Lost City (30°… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
167
4
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 190 publications
(179 citation statements)
references
References 102 publications
(116 reference statements)
6
167
4
2
Order By: Relevance
“…Conversely, some other studies reported the absence of organic compounds in hydrothermal fluids except at the Lost City alkaline vent field which is theoretically more favourable for abiotic synthesis [36]. Nevertheless, we report here the presence of semivolatile organic compounds in hydrothermal fluids from the Wallis and Futuna area and provide concentrations of a selection of extractable compounds that have been identified elsewhere as hydrothermally derived [27,37]: n-alkanes, n-fatty acids (n-FAs), mono-, and polyaromatic hydrocarbons (BTEXs and PAHs). These very first quantitative field data might feed thermodynamic models of abiotic synthesis, guide the design of experiments to better understand hydrothermal organic geochemistry, and help assessing the importance of hydrothermally derived organic compounds in metal complexation and, as a nutrient for microorganisms, complete fluxes calculation and enter in the carbon cycle budget calculations.…”
Section: Geofluidsmentioning
confidence: 52%
See 1 more Smart Citation
“…Conversely, some other studies reported the absence of organic compounds in hydrothermal fluids except at the Lost City alkaline vent field which is theoretically more favourable for abiotic synthesis [36]. Nevertheless, we report here the presence of semivolatile organic compounds in hydrothermal fluids from the Wallis and Futuna area and provide concentrations of a selection of extractable compounds that have been identified elsewhere as hydrothermally derived [27,37]: n-alkanes, n-fatty acids (n-FAs), mono-, and polyaromatic hydrocarbons (BTEXs and PAHs). These very first quantitative field data might feed thermodynamic models of abiotic synthesis, guide the design of experiments to better understand hydrothermal organic geochemistry, and help assessing the importance of hydrothermally derived organic compounds in metal complexation and, as a nutrient for microorganisms, complete fluxes calculation and enter in the carbon cycle budget calculations.…”
Section: Geofluidsmentioning
confidence: 52%
“…Notably numbers of studies agree on the major ligand role of organics in metal stabilisation, transportation, bioavailability, and ore-forming but there are hardly any clues on the nature of these ligands in hydrothermal environments [16][17][18][19][20][21][22][23][24][25]. Organic compounds in hydrothermal fluids may come from marine dissolved organic matter (DOM) recycling [12,13], subsurface biomass degradation [26], entrainment of organic detritus from local recharge zones, and subsequent degradation, or abiotic formation in the deep subsurface [27][28][29][30]. The latter is supported by many theoretical [31][32][33] and experimental work summarised in two reviews [34,35].…”
Section: Geofluidsmentioning
confidence: 99%
“…In recent hydrothermal fields, however, organic matter becomes thermally altered and redistributed (Simoneit, 1993;Delacour et al, 2008;Konn et al, 2009). Laboratory experiments using marine DOM indicate that thermal alteration 10 already occurs at temperatures >68-100°C, and efficient removal of organic molecules at 212-401°C (Hawkes et al, 2015(Hawkes et al, , 2016.…”
mentioning
confidence: 99%
“…Serpentinite-hosted hydrothermal systems -analogous to those of the Combin Zone where the investigated sepiolite was collected -are ideal sites for the production of abiogenic hydrocarbons via the FT-t reaction, by means of progressive polymerization and polycondensation reactions (Konn et al, 2009;Taran et al, 2007). Since a widely accepted hypothesis for sepiolite genesis involves direct precipitation from an aqueous solution saturated with Mg and silica (Jones and Galán, 1988;Galán and Pozo, 2011) and with an insignificant Al activity (Birsoy, 2002), the Perletoa sepiolite probably originated from a similar process.…”
Section: Origin Of Aliphatic Hydrocarbons and Sepiolite Genesismentioning
confidence: 99%